Water kefir, a fermented beverage containing probiotic microorganisms: From ancient and artisanal manufacture to industrialized and regulated commercialization - Moretti, Ana Florencia (2022)
Throughout the COVID-19 pandemic, there was a demand for natural products able to enhance consumers health. Many people discovered the benefits of fermented products such as milk and water kefir and kombucha. Specifically, water kefir has aroused great interest from people interested in consuming foods that do not come from animals (plant-based and vegan diets) or people allergic to milk proteins or lactose intolerant, while increasing the scientific evidence of water kefir health enhancement. This review deals with the needing for the establishment of quality parameters found in traditional and flavoured water kefir drink, for their implementation in the industrially produced beverage. Such industrialization must seek the sustainable development of this economic activity for the implementation of circular economy guidelines. The benefits and safety of this non-dairy fermented drink have been demonstrated since its ancestral consumption and have been documented by many scientific works around the world. The scientific community must accompany this rapid advance of fermented foods containing probiotic microorganisms, given the changing priorities within the food industry. In addition, the quality parameters for the inclusion of this product in the Codex Alimentarius of many countries must be established, in order to regulate its production on an industrial scale and marketing.